STRATEGI BRANDING KOMUNIKASI POLITIK PARTAI NASDEM PADA PILKADA KOTA BANDUNG 2024 - Hermawan, Vera (Linimasa : Jurnal Ilmu Komunikasi, 2025)
In the Regional Elections and Presidential Elections, each party implements various political communication branding strategies in order to increase its popularity among voters in order to get the most votes. Not to forget, the NasDem Party also did branding in the regional elections in Bandung in an effort to achieve victory. This study aims to further examine the communication strategy of NasDem political party branding to achieve victory in the regional elections in the city of Bandung. Using the case study method, there are important notes from the results of this study, namely: NasDem Political Parties use several political communication branding strategies in order to intensively increase the popularity of parties and candidates in the eyes of voters, ranging from publications on various social media platforms, political party ambassadors, socialization and promotion of parties or candidates by party insiders, Building party narratives that contribute positively to development and be inclusive for all, politics without dowry, slogans and taglines "beberes Bandung", parties of all circles, and canvassing to visit various levels of society to get closer.